Influence of nitrogen and potassium on growth, yield and oil content of Kaempferia galanga L. - Pal, Partha Ghosh, P (Journal of Spices and Aromatic Crops, 2002)
An experiment to study the effect of nitrogen and potassium on growth and yield of kaempferia (Kaempferia galanga L.) under the shade of Arjun (Terminalia arjuna) plantation was carried out. Increased application of nitrogen and potassium significantly improved the leaf number, leaf area and dry matter accumulation. Higher dose of nitrogen (40 kg ha-1) and potassium (20 kg ha-1) significantly increased the rhizome yield and oil content. Amongst the various interactions, application of 40 kg nitrogen in combination with 20 kg potassium per hectare gave maximum yield (10.24 t ha-1).